ESKATOLOGI ISLAM DALAM SYAIR IBARAT DAN KHABAR KIAMAT Islamic Eschatology in Syair Ibarat and Khabar Kiamat - Novi Setyowati; Nuraini Isti Kusumah; Partini Partini; Puput Puji Lestari; Umi Amanah; Bani Sudardi; Roch Aris Hidayat (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2017)
Eschatology is a doctrine of theology concerned with the end of the world or end times. It is futuristic, that is to say, a doctrine directed to the future. Islam has pillars that everyone must have or often referred to as the pillars of faith. One of which is the belief in things that will happen in the future, especially life after death. Discussion about life after death is included in eschatology. This study is intended to describe the content of classical Malay texts; Syair Ibarat and Khabar Kiamat. The study of this text is done by approaching the eschatological concepts contained in the text. The findings are that this poem contains eschatological concepts, namely (1) death, (2) barzakh (a period or state between death and resurrection), (3) kiamat (doomsday), (4) resurrection day, (5) mahsyar (6) heaven, and (7) hell. The study of the concept of eschatology in the classical Malay texts of Syair Ibarat and Khabar Kiamat is a means to convince human beings about life after death.